Alleviation role of exogenous cadaverine on cell cycle, endogenous polyamines amounts and biochemical enzyme changes in barley seedlings under drought stress - Serkan Ozmen; Selma Tabur; Signem Oney-Birol (Scientific Reports, 2023)
Abstract Cadaverine (Cad), which has an independent synthesis pathway compared to other polyamine (PA) types, contributes to the health of plants by regulating plant growth and development, abiotic stress tolerance and antioxidant defense mechanisms. In this work, experiments were carried out to understand the effects of exogenous Cad (10 µM) application under drought stress (%22 PEG 6000) and without stress on cell cycle, total protein content, endogenous PA levels, and biochemical enzyme activities in barley (Hordeum vulgare cv. Burakbey) considering the potential of Cad to stimulate the drought-related tolerance system. Cad application in a stress-free environment showed an effect almost like low-impact drought stress, causing changes in all parameters examined compared to samples grown in distilled water environment (Control). The results clearly show that Cad applied against the negative effects of drought stress on all parameters creates a drought resistance mechanism of the plant. Accordingly, Cad applied together with drought stress increased the density of cells in the cell cycle (G1–S and S–G2 phases) and the amount of endogenous (spermidine 10% and spermine 40%) PAs. In addition, while superoxide dismutase (SOD) (5%), (CAT) (55%) and ascorbate peroxidase (APX) (18%) enzyme levels increased, a stress response mechanism occurred due to the decrease in total protein content (20%) and malondialdehyde (MDA) (80%). As a result, exogenous application of 10 µM Cad showed that it reduced the negative effects of drought stress on endogenous PA amounts, cell division and biochemical activities in barley.